Hubungan Kualitas Tidur dengan Peak Performance pada Atlet Atletik Tuban - Fajar Jaya Rosadi; Roy Januardi Irawan; Catur Supriyanto; Heri Wahyudi (Mutiara Pendidikan dan Olahraga, 2025)
Remember sleep quality has a big impact on an athlete's best performance, this study aims to find out the relationship between sleep quality and peak performance, and how much sleep quality contributes to peak performance. To achieve peak performance, an athlete must be in optimum condition during training and matches. This research uses a quantitative descriptive research type with a correlational approach. Quantitative research collects and analyzes data using numbers and measurements. The researcher used purposive sampling, where the sample consists of 30 athletes from Ronggolawe Athletics Club in Tuban. The tools used in this study are the sleep quality scale and the peak performance scale, both administered through questionnaires. The data analysis method used is the product moment correlation test. The results of the data analysis showed a correlation coefficient of -0.423 (r = -0.423). Based on the analysis of the coefficient of determination, it was found that the sleep quality variable contributes effectively to the peak performance variable by 17.9%, while the remaining 82.1% comes from other factors not studied in this research.